The Satisfaction of Employees in Tishreen university with Health Insurance Services And itsreleastionship with demographic variables "A Field Study to survey a sample of Tishreen University Employees" (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The study aims to review the opinions of Tishreen university employees about the services provided by health insurance, and to identify the influencing factors that determine theirsatisfaction level with those services,Data was collected using a questioneer that was developed for the purposes of the study. The designed standard included indexes to measure satisfaction level with the different services included in health insurance program provided to the employees in Education and Higher Education sectors in Syria. Data was collected using Convenience Sample method, the study was limited to the employees benefit from health insurance services, and the research specimen includes (193) employees (25) of them are workers, (126) are administrative employees, (13) are technical body members, and (29) are teaching body members,data analyzing was done using the Statistical Package for Social Sciences program SPSS to reach the results of research. The research results have showed: a decrease in the satisfaction level with the health insurance services provided to the individuals in the studied specimen, and the importance of education level and work type in determining employee's satisfaction level with services.